(untitled) (Revista Brasileira de Contabilidade e Gestão, 2025)
This paper evaluates the effectiveness of fundamental analysis as a mechanism to reduce the effects of information asymmetry in the capital market in Mozambique. To achieve this objective, a questionnaire was developed on the quality of accounting information and the main fundamental indicators most used in the Mozambican capital market, aimed at investors and capital market analysts. A regression analysis was performed with panel data between the fundamental indicators (VPA, EPS, DY, P/E and ROE) and the logarithm of the share price, and the intrinsic value was calculated using Benjamin Graham’s formula to relate its movements to share prices. The results suggested that the main fundamental indicators used in Mozambique are P/E, DY and ROE. The main factors that define the quality of accounting information are transparency, auditing and comparability. The results showed that all fundamental indicators used influence 52.54% of the variability of the logarithm of the share price, however, only P/L, VPA and ROE were significant at 5%. The results also showed that the persistence of divergences between the intrinsic value and the share price suggests the need to improve the dissemination and access to accounting and fundamental information. However, overall, the results suggested that fundamental analysis is a tool that can reduce the effects of information asymmetry in the capital market in Mozambique